Neuropsychological manifestations in patients with epilepsy of the National Institute of Neurological Sciences - Cuenca Alfaro, José (2017)
We evaluated 216 people diagnosed with epilepsy in order to identify their neuropsychological characteristics, as well as to compare them according to gender, age group and time of illness. A registration form was applied for sociodemographic data and neuropsi (neuropsychological test battery in Spanish). The results indicated that 75 % of the sample presented normal neuropsychological manifestations, followed by 71 % of mild manifestations, 38 % moderate and 31 % severe. There are no differences by gender, but by age group and disease time.